INEFISIENSI BIAYA PRODUKSI DITINJAU DARI KUALITAS BAHAN BAKU DAN KUANTITAS PRODUK CACAT PADA PT. PANCARAN SEMANGAT JAYA DI SURABAYA - Dwi Widajati (Journal of Business & Banking, 2012)
PT. Pancaran Semangat Jaya, a manufacturing company, produces magazines named Panjebar Semangat (Java magazine, there are product defects at a maximum of 36, 177 in 2003 and lowest 31, 229 in 2005). Product defects are often caused by raw material quality that is not good. To avoid any mistakes, the company had to choose a good raw material prior to rocessing. The purpose of this research was to test and prove empirically the influence of raw material quality towards the quantity of product defect to production cos inefficiency. In this study, the analysis was done by collecting the data exploits quantity of raw material quality, the quantity of product defects and production costs. Simple regression analysis and multiple linear regressions were used to determine the effect of raw material quality and quantity of product defect to production cost inefficiency. The result showed that when the variable raw material quality was removed, the variable quantity of product defect would not influence the production cost inefficiencies. When the variable quantity of product defect was removed, the raw material quality would not either influence the production cost inefficiencies. Also the test results showed that the raw material quality and the quantity of product defect had no influence towards production cost inefficiencies.